Searching for new paradigms in a globalized world: Business ethics as a management strategy - Ogrean, Claudia; Herciu, Mihaela; Belaşcu, Lucian (Journal of Business Economics and Management, 2008)
The process of globalization is an undeniable reality of today’s world. Yet, paradoxically, the cornerstone of this phenomenon, economic performance, varies widely across the world whatever indicator (for example, GDP/habitant, competitiveness) we choose to use to compare countries. Increasingly, studies tend to explain this apparently paradoxical situation with reference to the issue of corruption and ethics. In essence, corruption is perceived to be an important impediment to the economic development of a country (or area). Many studies of corruption are focused at the national level. The aim of this conceptual paper is to explore the role of the firm (as opposed to national states or international institutions) as an influence on national corruption. We call for firms to reconsider their behavior regarding corruption, particularly in relation to their relationships with their stakeholders. We argue that by focusing on issues such as cooperation and stakeholder theory, a firm will change the way it does businesses by reducing private‐to‐public as well as private‐to‐private corruption and incorporating business ethics into its management strategies. First published online: 14 Oct 2010